Negara dalam Narasi: Analisis Framing Politik LKBN ANTARA terhadap Pemerintahan Prabowo–Gibran Dibandingkan Kompas.com - Reihan, Reza Alerio; Wijaya, Endika; -, Yulianti; Khafiza, Adiba Nur (PRoMEDIA, 2025)
This research analyzes the framing patterns of political news coverage by the Indonesian state news agency, LKBN ANTARA, in reporting on the Prabowo–Gibran administration, and compares it with the framing used by private media, Kompas.com. The study employs a qualitative approach using Robert N. Entman’s framing analysis method, comprising four elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings reveal that ANTARA tends to frame news affirmatively toward the government, emphasizing optimism and successful programs, while Kompas.com demonstrates a more pluralistic and critical framing pattern. This difference has implications for public discourse and political literacy in Indonesia.